Probe, Optical Emission and Quartz Crystal Microbalance Diagnostics in Hollow Cathode Magnetron - Usatov, I. I.; Poluektov, N. P.; Tsar’gorodsev, Yu P.; Evstigneev , A. G.; Kamyschov, I. A. (New Trends in Physical Science Research Vol. 1, 2022)
The purpose of this paper is to describe the characterization of an ionized physical vapor deposition (IPVD) by means of hollow cathode magnetron. Measurements with the Langmuir probe, optical emission spectroscopy, and grid quartz crystal microbalance were used to investigate a mechanism for the production of excited argon and copper atoms and ions. The kinetic processes of excitation were considered, and the main processes were ascertained using measurement results. The pressure range was 0.5 - 10 mTorr with 1- 5 kW discharge power. Plasma parameters like electron densities and temperatures, electron energy distribution functions, plasma space and floating potentials as a function of position, pressure, and power in the growth chamber were calculated. The plasma density is up to 1012 cm-3 at 20 cm from the magnetron for 10 mTorr. Using a grid quartz crystal microbalance, the ionized copper flux fraction was measured as a function of the gas pressure, discharge power, and distance from the target. At gas pressures of higher than 15 mTorr, the degree of ionization at a distance of 31 cm exceeds 50%.